(untitled) (Research, Society and Development, 2021)
This study aimed to characterize physically, chemically, morphologically and thermally a soil in the region of Cariri Cearense in order to verify its quality for agricultural purposes. To this end, the following were performed: particle size analysis, actual particle density and moisture content, pH measurement, exchangeable acidity, organic matter content, metal determination, X-ray fluorescence (FRX), Fourier transform infrared (FTIR), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The results obtained were: (i) in chemical characterization it was observed conformity in the levels of Zn, whereas for Cr, Cu and Pb, they were superior to those of prevention CONAMA; Mn and Zn were found within the range for soils, but with a deficiency of the element Ni. For vegetables, Cu contents were above the range, while Mn and Zn were adequate. For Ni, ways to make up for its absence are recommended. The total levels of macronutrients Ca, K and Mg are within those exposed. The constituent oxides in higher concentrations were SiO2, Al2O3 and Fe2O3. The FTIR analysis showed bands of clay minerals and quartz, presence of water and organic matter, (ii) SEM images showed dispersed particles with varying sizes and irregular surfaces, (iii) the physical characterization showed a sandy loam texture and distribution with 12% clay, 7.25% silt, 74.91% sand and 5.84% gravel and (iv) the DSC analysis indicated events such as dehydration and decomposition of organic matter. Thus, it is necessary to constantly assess the fertility of the soil to survey the necessary nutrients depending on the introduced crop.